Evaluasi Sistem Pemenuhan Kebutuhan Bantuan dengan Melibatkan Sektor Swasta untuk Bencana Alam di Indonesia - Wongso, Randy Christian; Widyadana, I Gede Agus (Jurnal Titra, 2015)
This study aimed to evaluate the compliance system of the reliefs through Indonesia aid agencies. Reliefs can be assembled and deployed from the government, private, and community. Logistical support needed for disaster management. Support logistical support should be on time, precise location, target, good quality, enough quantity, and needed. This research used interview method to the BPBD, PMI, and the private sector (KSR) and distributing questionnaires to 101 respondents to identify the communitys involvement in the current disaster management system. Results from this study indicate that the compliance system of the goods through disaster management agencies still lack involve the private sector and community involvement in disaster management at the program is still lacking. The current system is still considered less troublesome and won the trust of the public. The private sector is still less involved in this system, whereas the private sector is a party that can assist humanitarian organizations that exist today to meet their needs. One of the private parties who may be involved is KSR University